Chemical diversity and biological activity of secondary metabolites in eight species of Curcuma - Ummul Mardiah Elias (2015)
Curcuma (Zingiberacae) are documented to originate from Indo-Malayan region and known to be a rich source of secondary metabolites with interesting pharmaceutical properties. There are at least eight species of this genus known to be utilized in the Malay community. However, not much information is available pertaining to its chemical composition nor of its biological potential. In this investigation, the volatile essential oil and its secondary metabolites were extracted, isolated and determined via chromatographic means. The essential oils were obtained by hydrodistillation and analyzed using GCMS. There were 49 compounds in C. aeruginosa (0.17%), 46 compounds in C. caesia (0.16%), 65 compounds in C. heyneana (0.23%), 25 compounds in C. longa (0.33%), 10 compounds in C. mangga (0.19%), 15 compounds in C. rotunda (0.16%), 22 compounds in C. xanthorrhiza (0.36%) and 20 compounds in C. zedoaria (0.31%), which then be categorize into four group. Belonging to group one, C. aeruginosa, C. caesia, C. longa and C. xanthorrhiza, contains high composition of oxygenated sesquiterpenes while in group (2), C rotunda and C. zedoaria have high content of oxygenated monoterpenes. By having high content of hydrogenated sesquiterpenes and hydrogenated monoterpenes., C. heyneana and C. mangga were placed in group 3 and 4, respectively. On the other hand, rhizome extract derived via soxhlet and analyzed through PTLC and NMR, revealed presence of 8 compounds in C aeruginosa (5.81%) and C caesia (7.56%), 7 compounds in C. heyneana (3.32%), 6 compounds in C longa (3.11%), 2 compounds in C mangga (1.92%), 5 compounds in C. rotunda (2.07%), 6 compounds in C. xanthorrhiza (3.23%) and 6 compounds in C. zedoaria (3.72%). Analysis on type of compouds showed that C. aeruginosa and C. caesia belong to group 1 (germacrane, carabrane, guaiane and elemene), C zedoaria in group 2 (germacrane and elemene), C heyneana, C mangga, C longa, and C xanthorrhiza in group 3 (diphenylheptanoid) and C rotunda in group 4 (monoterpenoids). In addition, cude extract and essential oil of Curcuma sp. (1mg/ml) were evaluated for their biocidal activity againts food-borne bacteria. Essential oil of C. xanthorrhiza showed good inhibition zone againts Vibrio parahaemolyticus Furthermore, via MIC and MBA testing, essential oil of Curcuma exhibit ; i) bakteriostatic agent-C mangga, C rotunda and C zedoaria, ii) Bactericidal agent- C heyneana, C longa and C xanthorrhiza against Staphylococcus aureus. While, essential oil of Curcuma exhibit; i) Bakteriostatic agent-C heyneana, C mangga, C rotunda and C zedoaria, ii) Bactericidal agent -C longa dan C. xanthorrhiza againts MRSA. Moreover, it was also found moderate anticancer activity from compounds isolated from Curcuma sp.; compound 9 and 10 against MCF-7 cell, and compound 7,10,11 and 12 against HeLa cell lines.